Experimental optimization of the Nafion® ionomer content in the catalyst layer for polymer electrolyte membrane water electrolysis at high temperatures - Li, Hua; Huang, Senrui; Guan, Chao; Wang, Huixuan; Nakajima, Hironori; Ito, Kohei; Wang, Yulin (Frontiers in Energy Research, 2023)
The polymer electrolyte membrane water electrolysis (PEMWE) performance is closely related to the Nafion® ionomer content in catalyst layers (CLs). This study experimentally investigates the impact of anode and cathode Nafion® ionomer contents on the PEMWE performance at high temperatures. The Nafion® ionomer content is 5–30 wt% on both anode and cathode sides, while the temperature and operating pressure change from 80°C to 120°C and 0.1 MPa to 0.3 MPa, respectively. Experimental results reveal that elevated temperature and operating pressure can remarkably promote the performance of PEMWE with a reasonable Nafion® ionomer content and without dehydrating the membrane at 120°C and 0.3 MPa. However, the PEMWE performance deteriorates as the Nafion® ionomer content is too low. The anode Nafion® ionomer content has a relatively great impact on ohmic resistance, concentration, and activation overpotential, especially the concentration overpotential. Nevertheless, the cathode Nafion® ionomer content only affects the ohmic resistance. Finally, under the operating conditions of 120°C and 0.3 MPa, employing a Nafion ionomer content of 10 wt% in the anode–cathode sides minimizes the electrolysis voltage to 2.18 V at 18 A/cm2.